Corrigendum to: Optimization of bio-based cellulose–phosphate hydrogel production from rice husk waste using the Taguchi method - Selvia Aprilyanti; Irnanda Pratiwi; Winny Andalia; Tine Aprianti; Hariman Al Faritzie (Universitas Negeri Padang, 2026)
This Corrigendum relates to the following article: Selvia Aprilyanti, Ahmad Yani, M. Yusuf, Optimization of Bio-Based Cellulose-Phosphate Hydrogel Production from Rice Husk Waste Using the Taguchi Method. Teknomekanik, 9(1), 77–90 (2026). https://doi.org/10.24036/teknomekanik.v9i1.47172 Following publication of the above article, the authors identified several editorial inaccuracies requiring formal correction. These corrections include the addition of missing cross-references to Figures 3–7 within the manuscript text, revision of the schematic presented in Figure 3, correction of the caption and interpretation of Figure 5, and correction of the magnification information reported in the caption of Figure 7. These corrections improve the clarity and internal consistency of the published article and do not affect the experimental data, statistical analyses, results, scientific interpretation, or conclusions of the study.